The influence of restricted visual feedback on dribbling performance in youth soccer players - Fransen, J.; Lovell, T. W. J.; Bennett, K. J. M.; Deprez, D.; Deconinck, F. J. A.; Lenoir, M.; Coutts, A. J. (Motor control, 2017)
The aim of the current study was to examine the influence of restricted visual feedback using stroboscopic eyewear on the dribbling performance of youth soccer players. Three dribble test conditions were used in a within-subjects design to measure the effect of restricted visual feedback on soccer dribbling performance in 189 youth soccer players (age: 10-18 y) classified as fast, average or slow dribblers. The results showed that limiting visual feedback increased dribble test times across all abilities. Furthermore, the largest performance decrement between stroboscopic and full vision conditions was in fast dribblers, showing that fast dribblers were most affected by reduced visual information. This may be due to a greater dependency on visual feedback at increased speeds, which may limit the ability to maintain continuous control of the ball. These findings may have important implications for the development of soccer dribbling ability. ABSTRACT FROM AUTHOR